DELIMITING JUSTICE: ANIMAL, VEGETABLE, ECOSYSTEM? - PEPPER, ANGIE (Les ateliers de l'éthique / The Ethics Forum, 2018)
This paper attempts to bring some clarity to the debate among sentientists, biocentrists, and ecocentrists on the issue of who or what can count as a candidate recipient of justice. I begin by examining the concept of justice and argue that the character of duties and entitlements of justice sets constraints on the types of entities that can be recipients of justice. Specifically, I contend that in order to be a recipient of justice, one must be the bearer of enforceable moral claim rights. I then suggest that this has important implications for the dispute among sentientists, biocentrists, and ecocentrists. In brief, I show that sentientists cannot exclude nonsentient entities from the domain of justice merely by denying that they have “the right kind of interests,” and biocentrists and ecocentrists cannot move seamlessly from some feature of living things or ecosystems to entitlements of justice. I further argue that ultimately this disagreement on the bounds of justice bottoms out in a normative disagreement about which entities possess moral claim rights, and that the case for biotic or ecosystem rights has yet to be convincingly established.